Application of integrated vitrinite reflectance and FAMM analyses for thermal maturity assessment of the northeastern Malay Basin, offshore Vietnam: Implications for petroleum prospectivity evaluation - Petersen, H.I.; Sherwood, N.; Mathiesen, A.; Fyhn, M.B.W.; Dau, N.T.; Russell, N.; Bojesen-Koefoed, J.A.; Nielsen, L.H. (Marine and petroleum geology, 2009)
Several exploration wells have intersected a Cenozoic coal-bearing, fluvial-deltaic mudstone and sandstone succession in the northeastern Vietnamese part of the Malay Basin, and have successfully tested seismically identified direct hydrocarbon indicators (DHIs). The oil and gas/condensate discovery well 46-CN-1x encountered a ∼55 m thick section of lacustrine mudstones having considerable potential as an oil source. Vitrinite reflectance (VR) measurements from these alginite-bearing rocks introduce several problems in thermal maturity evaluation, including associated VR suppression and delineation of cavings and bitumens. Reliable thermal maturity gradients, however, may be established using a combination of conventional VR measurements and ‘equivalent VR’ (EqVR) values derived from the fluorescence alteration of multiple macerals (FAMM) technique. These measurements, performed on dispersed organic matter (DOM) in cuttings from 46-CN-1x, allow separation of low-reflecting bitumens and vitrinite in cavings from indigenous vitrinite and the FAMM results indicate VR suppression of 0.14% in an alginite-bearing mudstone with a high Hydrogen Index value. On the basis of available ‘raw’ VR data, a highly irregular maturity trend is determined, with the deepest sample (2675–2680 m) having a VR of ∼0.4%R o. The EqVR value, however, for the deepest sample is 0.70%. The maturity trend determined from the FAMM data (and VR data, omitting samples having suppressed VR) indicates that the top of the oil window (VR of 0.75%R o) is located at about 2800 m depth. Modelling the geothermal gradient using the EASY%R o algorithm yields ∼40 °C/km for both of the two maturity profiles; this is in the low end of the range for the Malay Basin. Modelled temperature histories indicate onset of hydrocarbon generation for the uppermost Oligocene source rocks between 2 Ma and present-day, which post-dates trap formation. Seismic facies patterns suggest that lacustrine oil-prone units are in the oil window in the same graben complex a few km NW of the investigated well, and these rocks are likely to be the source of the hydrocarbons found in the well. A more widespread occurrence of hydrocarbons sourced from this kitchen is indicated by other discoveries and mapping of DHIs in the area.